Growth Regression and Economic Theory - Chris Elbers; Jan Willem Gunning (Tinbergen Institute, 2002)
In this note we show that the standard, loglinear growth regression specificationis consistent with one and only one model in the class of stochastic Ramsey models. Thismodel is highly restrictive: it requires a Cobb-Douglas technology and a 100% depreciationrate and it implies that risk does not affect investment behavior.
Keywords: O4; D91; 330; economic growth; growth regressions; growth under uncertainty; Wachstumstheorie; Regression; Wissenschaftliche Methode; Theorie